Síntese e propriedades de novos fragmentos de leptina - Pereira, Jádson Moreira [UNIFESP] (2010)
Leptin, a protein hormone secreted by the adipose tissue, is responsible for signaling the nutritional status of the body to the central nervous system and partly by the regulation of energetic metabolism, as well as being involved in various physiological processes. The absence or resistance of leptin to the organism causes obesity, diabetes and hypogonadism. The tertiary structure of the leptin molecule reveals the presence of four helices, whose pattern is typical of cytokines. Starting from the peptide sequence Ac-[Ser96]-hLEP89-98-NH2 described by Martins and coworkers (2006), we designed a new series of ten peptide fragments derived from the leptin with punctual substitutions of L-to D-amino acid. The peptides were synthesized by the manual solid phase method by employing the t-Boc strategy. They were purified by high performance liquid chromatography and characterized by liquid chromatography coupled to mass spectrometry. In order to correlate structure with biological activity of the fragments conformational studies of the peptides were performed by Circular Dichroism in different solvent media. The effects of intracerebroventricular injections of solutions of the peptides in the variations of food intake and body weight were evaluated in male Wistar rats. Furthermore, the effect caused by the fragments in the blood glucose levels were also assessed, as well as the stabilities of the compounds against the action of proteases present in plasma. Among the compounds studied, the best results were obtained with the fragment Ac-[Ser96, D-Phe92]-hLEP89-98-NH2, which proved to be more stable in plasma and showed biological activity (changes in weight and food intake and hypoglycemic effect) equipotent those observed with the fragments [D-Leu4]-OB3 and Ac-[Ser96]-hLEP89-98-NH2, the most active peptides described in the literature so far. Conformational studies by Circular Dichroism, however did not allow us to establish direct correlation between structure and biological activity of the fragments. Although there is a need for refinements, this approach may offer an interesting basis for the development of compounds correlated with leptin with potential application in studies of human obesity or in veterinary medicine.